Association between violence and mental distress, self-harm and suicidal ideation and attempts among young people in Malawi. Issue 5 (6th May 2022) - Villaveces, Andrés; Shankar, Viswanathan; Palomeque, Francisco; Padilla, Mabel; Kress, Howard
Abstract : Background: Mental health problems ranging from depression to more severe acts such as self-harm or suicidal behaviours are a serious problem among adolescents and young adults. Exposure to violence during the life of young people can increase mental health issues for youth. This study examines the relationship between exposure to violence and mental health issues among youth using a nationally representative study in Malawi. Methods: We analysed data from the nationally representative Violence Against Children Survey from Malawi (2013) to quantify the association between exposures to violence (physical, sexual and emotional) and their relationship with mental distress, self-harm behaviours and suicidal ideation and attempts among youth aged 13–24 years. We evaluated the association of exposures to violence against children with reported mental health conditions among women and men. We used ordinal logistic regression models with appropriate survey weights to assess exposures to violence and the three outcomes of interest. Results: Children and youth aged 13–24 years exposed to violence in childhood reported higher levels of adverse mental health effects, including mental distress, self-harm behaviours and suicidal ideation and attempts. The odds of reporting these outcomes increased as the number of violence types increased. Conclusions: Understanding the risks based on different combinations of exposures to violence in Malawi can help identify populations at higher risk and optimise violence prevention strategies.